Comparative Analysis of the Perioperative Period in High-Risk Cardiac Surgery Patients with Stable and Unstable Angina Pectoris - Gogayeva, Olena K.; Rudenko, Anatoliy V.; Klymenko, Larysa A.; Lazoryshynets, Vasyl V. (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To analyze the features of the perioperative period in cardiac surgery patients with stable and unstable angina. Materials and methods. Retrospective analysis of random 194 cardiac surgery patients with coronary artery disease (CAD) and EuroSCORE II > 5%, who were operated and discharged from the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine from 2009 to 2019. All the patients underwent standard clinical, laboratory and functional tests, coronary angiography and coronary artery bypass grafting (CABG). Results. When assessing the initial clinical picture of randomized patients, 110 (56.7%) were diagnosed with stable angina, and 84 (43.2%) with unstable. On admission, acute myocardial infarction (AMI) was diagnosed in 12 (14.3%) patients (p < 0.0001), and among patients with stable angina 91 (82.7%) had a history of AMI (p = 0.0158). All the patients had polymorbidity: the Charlson comorbidity index was 5.7 ± 1.8 in patients with unstable angina and 5.9 ± 1.9 in stable CAD (p = 0.4583). Patients with unstable angina were more likely to have subocclusive-occlusive lesions of the left main coronary artery (p = 0.0083), left anterior descending artery (p = 0.0392) and left circumflex artery (p = 0.0387). All the patients were discussed by the cardiac team prior to surgery which was performed by experienced cardiac surgeons with 24 ± 12.5 years of experience. Emergency surgery was performed in 43 (51.1%) patients with unstable angina and 12 (10.9%) with stable angina (p <0.0001), off-pump CABG was performed in 82 (97.6%) and 105 (95.4%) patients, respectively (p = 0.4231). The postoperative period in patients with unstable angina was almost no different from that in patients with stable CAD. The patients with unstable angina were discharged on average on day 8.7 ± 4.04, and those with stable CAD were discharged on day 8.2 ± 3.2 (p = 0.3373). Conclusions. The outcome of the operation depends on the quality of the heart team work and requires a highly qualified cardiac surgeon with sufficient experience. Performing CABG on a working heart minimizes the occurrence of perioperative complications in patients with both unstable and stable CAD.